2019
DOI: 10.3390/ijms20112838
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis Risk Associated with Head and Neck Cancer: A Review

Abstract: Venous thromboembolism (VTE) is a common complication for cancer patients. VTE-associated risk varies according to the type of tumor disease. Head and neck cancer is a common cancer worldwide, and most tumors are squamous cell carcinomas due to tobacco and alcohol abuse. The risk of VTE associated with head and neck (H&N) cancer is considered empirically low, but despite the high incidence of H&N cancer, few data are available on this cancer; thus, it is difficult to state the risk of VTE. Our review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 155 publications
7
55
0
Order By: Relevance
“…Incidence of VTE in H&N cancer patients after surgery is generally low (0 ~ 8%), although one study reported higher rate of 26.3% (18,20). While one study reported that H&N cancer is the least common type of cancer diagnosed following VTE, another large study identi ed H&N cancer as the second highest risk for VTE among 18 types of carcinoma (18,19). In a large population-based study, the incidence of TEE in noncancer population was 1.4%, which is similar to the rate of occurrence among H&N cancer patients reported in several studies (18,25).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Incidence of VTE in H&N cancer patients after surgery is generally low (0 ~ 8%), although one study reported higher rate of 26.3% (18,20). While one study reported that H&N cancer is the least common type of cancer diagnosed following VTE, another large study identi ed H&N cancer as the second highest risk for VTE among 18 types of carcinoma (18,19). In a large population-based study, the incidence of TEE in noncancer population was 1.4%, which is similar to the rate of occurrence among H&N cancer patients reported in several studies (18,25).…”
Section: Discussionmentioning
confidence: 98%
“…Con icting results have been reported regarding the incidence of TEE in H&N cancer patients. According to one meta-analysis, the incidence of VTE in H&N cancer patients was 0.16-3.13% (18). Incidence of VTE in H&N cancer patients after surgery is generally low (0 ~ 8%), although one study reported higher rate of 26.3% (18,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney, uterus, bladder, lung, colon [35] as well as hematologic malignancies are associated with relatively high risk of thrombosis [37]. Lower risk of thrombotic event is suspected for patients with breast, head and neck or prostate cancer [37,38]. Especially in the treatment of lung, mediastinal, head and neck cancer, the radiation field can involve the PICC and the corresponding venous vessel.…”
Section: Discussionmentioning
confidence: 99%